Why can’t children with autism integrate into society in China? Study based on the perspective of NGO classification - Li, Zhiwei; Qi, Caiyun (Frontiers in Public Health, 2023)
Introduction In the field of protecting children with autism, NGOs have become a major force that cannot be ignored. Although NGOs for children with autism have expanded the number and improved the quality of the services they provide, a large number of autistic children still cannot achieve the goal of social inclusion in China. The existing literature has mostly tried to explain the reason from the perspective of the common characteristics of NGOs and has paid insufficient attention to the huge differences between these NGOs, so it is impossible to identify the obstacles that children with autism encounter accurately. Methods From the perspective of NGO classification, this study conducted an in-depth investigation of 4 NGO cases in City N, China, to show the impact of the difference of NGOs on the obstacles to the social inclusion of autistic children. Results The research has found that under the authoritarian regime, NGOs for children with autism that rely heavily on external funds include three common groups: government-oriented NGOs, foundation-supported NGOs, and individual-financed NGOs. The structural characteristics of the funders and their interaction with the NGOs for children with autism shape their different action logics, as the result that the desire of children with autism to integrate into society cannot be achieved as expected. Discussion The results of this study give more accurate insights into the barriers in social service provision for children with autism that impede their social inclusion and provide a reference for those seeking a solution to this problem.